2018
DOI: 10.1038/s41586-018-0552-x
|View full text |Cite
|
Sign up to set email alerts
|

Erythro-myeloid progenitors contribute endothelial cells to blood vessels

Abstract: The earliest blood vessels in the mammalian embryo are formed when endothelial cells (ECs) differentiate from angioblasts and coalesce into tubular networks. Thereafter, the endothelium is thought to expand solely by proliferation of pre-existing ECs. Here we show that the earliest precursors of erythrocytes, megakaryocytes and macrophages, the yolk sac-derived erythro-myeloid progenitors (EMPs), provide a complementary source of ECs that are recruited into pre-existing vasculature. Whereas a first wave of yol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
145
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(161 citation statements)
references
References 59 publications
(100 reference statements)
14
145
1
1
Order By: Relevance
“…Future work should help determine if distinct regions within the mesoderm can give rise to functionally divergent subsets of angioblasts. Plasticity of EC development is further illustrated from recent work that surprisingly showed that extraembryonic derived erythomyeloid progenitors can give rise to up to 60% of liver ECs in mice (Plein et al, 2018). progenitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work should help determine if distinct regions within the mesoderm can give rise to functionally divergent subsets of angioblasts. Plasticity of EC development is further illustrated from recent work that surprisingly showed that extraembryonic derived erythomyeloid progenitors can give rise to up to 60% of liver ECs in mice (Plein et al, 2018). progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral plate mesoderm (LPM) is known to be the primary source of ECs across vertebrate phyla (Potente and Makinen, 2017). However, recent findings have suggested that ECs can arise from distinct mesodermal derivatives, including extraembryonicderived erythromyeloid progenitors (EMPs), that contribute extensively to the murine kidney vasculature (Plein et al, 2018). Similarly, there is evidence in rodents and other amniotes, that paraxial mesoderm (PM) also generates a contingent of ECs that contribute to the embryonic vasculature (Ambler et al, 2001;Esner et al, 2006;Noden, 1989;Pardanaud et al, 1996;Pouget et al, 2006;Pouget et al, 2008;Wilting et al, 1995;Yvernogeau et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports addressing EPCs and disease, such as systemic sclerosis, showed contradictory and discrepant results about EPCs mobilization and differentiation; in part, because there is a lack of a precise panel of cell surface markers used for the characterization of this subset of cells [4][5][6][7][8][9][10]. In mouse embryonic vascular endothelium, erythro-myeloid progenitors (EMPs) can differentiate into ECs [11] and in a mouse model of carotid injury, monocytes (CD14 + cells) are capable of improving re-endothelialization [12]. In vivo and in vitro targeting of Tie2-monocytes decreases angiogenesis by abrogating EC proliferation [13][14][15] and an in vivo CCR2 (chemokine (C-C motif) receptor 2) knockout impairs monocytes recruitment and VEGFA (also named VEGF, vascular endothelial growth factor) expression, accompanied by a reduction in the angiogenesis rate [16].…”
mentioning
confidence: 99%
“…1, yellow labels). In Plein et al, the vasculature of the embryo is shown to develop from two distinct lineages: in addition to mesoderm-derived ECs, the authors observed that a complementary source of endothelium is recruited into the pre-existing vasculature through transdifferentiation of erythro-myeloid progenitors (EMPs) that emerge in the yolk sac [32]. Although this updated strategy yielded cells that harbour all hallmarks of HSCs, the reprogramming efficiency was still very low (~0.6%).…”
Section: Direct Conversion Of Somatic Cells To Haematopoietic Stem Anmentioning
confidence: 99%
“…Recent work on the heterogeneous origin of the cells that comprise adult blood vessel endothelium may offer some clues to explain such a low reprogramming rate. In Plein et al, the vasculature of the embryo is shown to develop from two distinct lineages: in addition to mesoderm-derived ECs, the authors observed that a complementary source of endothelium is recruited into the pre-existing vasculature through transdifferentiation of erythro-myeloid progenitors (EMPs) that emerge in the yolk sac [32]. This distinct lineage persists into adulthood, raising the possibility that vascular endothelium acts as a functional mosaic, where a distinct lineage may be more amenable to haematopoietic reprogramming than others.…”
Section: Direct Conversion Of Somatic Cells To Haematopoietic Stem Anmentioning
confidence: 99%